2023
DOI: 10.1002/adem.202201778
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Corrosion Behavior of Biodegradable Mg–0.5Zr–0.5Ca–xZn Magnesium Alloys

Abstract: Mechanical properties and in vitro corrosion behavior of biodegradable Mg–0.5Zr–0.5Ca–xZn alloys in the simulated body fluid (SBF) solution are investigated. Zinc addition leads to a remarkable grain refinement in the as‐cast condition, as well as the formation of Ca2Mg6Zn3 and Mg7Zn3 compounds. As a result, the lean Mg–0.5Zr–0.5Ca–1Zn alloy shows the best combination of mechanical properties with an ultimate tensile strength (UTS) of 182 MPa, total elongation of 9.5%, and tensile toughness of 13 MJ m−3, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Based on this principle, Zn is widely used in Mg materials. Numerous studies [ 12 , 13 , 14 , 15 ] have found that Zn can simultaneously improve mechanical properties and corrosion resistance. Hence, Mg-Zn alloys have attracted great interest from many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this principle, Zn is widely used in Mg materials. Numerous studies [ 12 , 13 , 14 , 15 ] have found that Zn can simultaneously improve mechanical properties and corrosion resistance. Hence, Mg-Zn alloys have attracted great interest from many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Studies have been performed by various groups around the world to improve the mechanical properties of Mg-based alloys to expand their applications by alloying additions. [10][11][12][13][14][15][16] For example, Ghorbani et al designed the Mg-0.5Zr-0.5Ca-1Zn alloy, exhibiting significant improvement in the ultimate tensile strength, elongation, tensile toughness, and corrosion resistance in comparison with the Mg-0.5Zr-0.5Ca alloy. [10] The Mg-10Li-3Al-2.8Zn alloy was reported to have superior yield strength of 321 MPa and ultimate tensile strength of 346 MPa by Wang et al, [15] after undergoing cold rolling, annealing, and water quenching.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16] For example, Ghorbani et al designed the Mg-0.5Zr-0.5Ca-1Zn alloy, exhibiting significant improvement in the ultimate tensile strength, elongation, tensile toughness, and corrosion resistance in comparison with the Mg-0.5Zr-0.5Ca alloy. [10] The Mg-10Li-3Al-2.8Zn alloy was reported to have superior yield strength of 321 MPa and ultimate tensile strength of 346 MPa by Wang et al, [15] after undergoing cold rolling, annealing, and water quenching. These authors further investigated the strengthening mechanism for this alloy and found the solution strengthening to be the most important contributor.…”
mentioning
confidence: 99%